Influences of wide-narrow seeding on soil properties and winter wheat yields under conservation tillage in North China Plain - Hu, Hongnan; Lu, Caiyun; Wang, Qingjie; Li, Hongwen; He, Jin; Xu, Dijuan; Wang, Xianliang (International Journal of Agricultural and Biological Engineering, 2018)
In order to promote the winter wheat yield and guarantee seeding quality in double-cropping system, no-tillage or reduced tillage planting modes with different row spacing have been implemented to result in different levels of yield. A three-year (2012-2015) field experiment was conducted on the experimental farm at Zhuozhou of Hebei Province in North China Plain to compare winter wheat yield from the two planting modes: wide-narrow row space planting mode (WN) and uniform row space planting mode (UR) Both planting modes were performed under reduced tillage conditions with straw mulching. The results showed that in North China Plain WN had positive impacts on crop yield, yield components, leaf area index (LAI) and intercepted photosynthetically active radiation (IPAR) index. Comparing with the UR, IPAR and LAI index for WN were enhanced by 4.8% and 5.2%, respectively. The average yield for WN was 7.2%, significantly greater than that of UR under the same quantity and density. In addition, for WN mode, machinery could pass through with less blocking under large amount of straw mulching, which largely improved tillage efficiency and potentially popularized the conservation tillage technology in North China plain. It is therefore recommended that wide-narrow row space planting mode (WN) combined with reduced tillage and straw mulching be more suitable for conservation tillage in double-cropping pattern areas in North China Plain.Keywords: winter wheat yield, wide-narrow seeding, conservation tillage, row spacing, LAI, IPARDOI: 10.25165/j.ijabe.20181104.3399Citation: Hu H N, Lu C Y, Wang Q J, Li H W, He J, Xu D J, et al. Influences of wide-narrow seeding on soil properties and winter wheat yields under conservation tillage in North China Plain. Int J Agric & Biol Eng, 2018; 11(4): 74–80.